ANALISIS LAPORAN KEUANGAN BERDASARKAN PSAK 109 PADA YAYASAN RUMAH YATIM ARROHMAN - Syamsul Hidayat; Anah Zanatun; Nani Rohaeni (Akuisisi: Jurnal Akuntansi, 2018)
The purpose of this study is determine whether the accounting treatment of zakat in Rumah Yatim Arrohman accordance with PSAK No. 109. This research is conducted to examine the financial statements prepared by Rumah Yatim Arrohman accordance with PSAK No. 109 on Accounting for Zakat. The method used is descriptive comparatif approach. The results of this research concluded that Rumah Yatim Mandiri have fully implemented use PSAK No.109. in presenting the financial statements. because in PSAK No. 109, zakah accounting aims to regulate the recognition, measurement, presentation and disclosure of transactions zakah, infaq/ Sadaqah.